Carbon Dioxide Separation From Binary Gas Mixture Containing High Carbon Dioxide Content By Pressure Swing Adsorption Utilizing Organic And Inorganic Adsorbents - Abdullah, Aman (2019)
Carbon dioxide (CO2) gas enrichment and separation process have been researched for decades and various methods are being applied in industries to reduce and resist CO2 gas due to its corrosive characteristics and negative effects on environment. Greenhouse gases such as methane (CH4) and CO2 are the most abundant in natural gas wells. They contribute significant negative effects to global warming. In this research, Pressure swing adsorption method was utilized as a mechanism to capture and recover binary gas via gas separation process by adsorbents. The adsorbents used in this study were Zeolite 5A, Zirconium-benzene dicarboxylate (UiO-66) and activated carbons made from Kenaf and palm kernel shell (PKS) within the pressure differences of up to 3 bars. The adsorbents were prepared and characterized using X-Ray Diffraction (XRD) analysis, Brunauer–Emmett–Teller (BET) analysis, Scanning Electron Microscope (SEM) analysis, Energy Dispersive X-Ray (EDX) analysis and particle size distribution analysis. Adsorbents selection and their capability were tested using binary mixture gas of 70% CO2 and 30% CH4 via breakthrough studies using volumetric method. The experimental data were collected by manipulating the adsorption and desorption time ranging up to 4 minutes. The results show that CO2 gas had higher affinity than CH4 for these adsorbents. Adsorbent saturation period declined towards increasing pressure and vice versa. Experimental data showed that activated carbon made from palm kernel shell yielded the optimum purity and recovery of CH4 and CO2 gases. Purity of CH4 and CO2 of 85% and 94% respectively were successfully achieved at recovery of CH4 and CO2 of 94% and 89% respectively. The other adsorbents were saturated quickly and less effective for high carbon dioxide content separation.